Selection and review of measurement item of student's learning environment - Seri Intan Mokhtar; Seri Bunian Mokhtar; Saemah Rahman (2011)
The learning environment plays important roles in the cognitive, effective and social students. Reviewing the learning environment is given due attention to this day because of its importance in helping to improve learning outcomes. This study will look at the selection and review of the measurement items of learning environment factors in Technical Institutions in the country. Variables to be examined in this study are assessment, teaching approaches, learning community, learning resources, work load, the clear objectives. Respondents consisted of 455 final semester engineering students. Data were analyzed descriptively for reliability (Cronbach Alpha values) and factor analysis was used to obtain 6 factor solutions (Eigenvalues and KMO) using SPSS 17 software. Results showed that 6 factor solutions with Eigen values above 1.0. The value of Kaiser-Meyer-Olkin Measure of Sampling Adequacy 0.868> 0.6 is adequate for inter-correlation while Barlett Test was significant (Chi Square = 5962.485, p <0.05). The anti-image correlation matrix by The Measure of Sampling Adequacy (MSA) is more than the value of 0.5. Items O2, PP6, PP7, PP5, P1, SP3 and SP4 dropped based on the criteria by Hair et al (2006), where each item should exceed the value of 0.50. Total variance explained for this loading was 61.51 %.